Oregano Herb Versus Oregano Essential Oil as Feed Supplements to Increase the Oxidative Stability of Turkey Meat - Florou-Paneri, P.; Palatos, G.; Govaris, A.; Botsoglou, D.; Giannenas, I.; Ambrosiadis, I. (International Journal of Poultry Science, 2005)
The objective of this study was to investigate the use of oregano herb versus oregano essential oil as feed supplements to increase the oxidative stability of turkey meat stored at 4oC. Thirty 12-week-old turkeys allocated into five groups were fed a control diet and diets supplemented with 5 g oregano herb/kg, 10 g oregano herb/kg, 100 mg oregano essential oil/kg, and 200 mg oregano essential oil/kg, for 4 weeks prior to slaughter. Lipid oxidation was assessed by monitoring malondialdehyde formation in breast and thigh meat at 0, 3, 6 and 9 days of refrigerated storage. Results showed that the feed supplements increased the oxidative stability of meat without exerting any effect on feed intake and daily weight gain of turkeys. Oregano essential oil supplementation at 100 mg/kg was more effective in delaying lipid oxidation compared to the control diet at all time points, but inferior to the oregano herb at 5 g/kg. Also, oregano essential oil at 200 mg/kg was more effective than the oregano herb at 5 g/kg and equivalent to oregano herb at 10 g/kg, in delaying lipid oxidation. Thigh meat was more susceptible to lipid oxidation compared to breast meat.